A Comprehensive Review of Multi-Use Platforms for Renewable Energy and Aquaculture Integration - Alexandra Ionelia Manolache; Gabriel Andrei (Energies)
This review aims to find, classify, and discuss ongoing projects that fall into the category of multi-use platforms, concerning offshore energy exploitation and marine resource production, including aquaculture. The term multi-use platforms (MUPs) refer to areas that may accommodate multiple operations such as aquaculture, tourism, transportation, oil, or energy production. This research only examines the current situation of marine energy projects that entail the integration of either a single kind of renewable energy or other types of marine renewable energy, in conjunction with aquaculture. The particularity of this research consists in the exclusive choice of platforms that integrate two sources of renewable energy on a single platform. The study focuses on analyzing the projects set up over time on these platforms, all of which include aquaculture. The state of the art in MUPs for offshore applications was examined to generate the review. We devised a methodical search approach aiming to find relevant material from various academic fields. During this phase, we looked to understand as much as we could about MUPs, including their design, the nature of these projects, what kinds of projects they can include, how they integrate renewable energy sources, and whether aquaculture facilities can be put together. To preserve scientific integrity and guarantee the inclusion of relevant research, a search strategy was formulated. The bibliographic study was through critical analysis, and at the end, significant conclusions were drawn concerning the development of multi-use platforms.